Pengaruh Penerapan Metode Ceramah terhadap Implementasi Nilai-nilai Akhlak pada Siswa di Kelas 9 MTs Satu Atap Datok Sulaiman Putra Palopo - Wisran, Rijal Ramadhan; RN, Bustanul Iman; Amin, Agil (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to determine the effect of the lecture method on the implementation of moral values among ninth-grade students of MTs Satu Atap Datok Sulaiman Putra Palopo and to identify the factors influencing its effectiveness. The research employed a quantitative approach with a quasi-experimental design of the Nonequivalent Control Group Design type. The sample consisted of 51 students selected through a simple random sampling technique. The research instruments included a Likert-scale questionnaire and observation sheets, while data analysis utilized descriptive statistical techniques complemented by the t-test, simple linear regression analysis, and the determination coefficient (R²). The findings revealed a significant influence between the application of the lecture method and the implementation of students’ moral values. The experimental group achieved an average post-test score of 82.4, categorized as high, while the control group obtained an average score of 74.5, categorized as moderate. The t-test results indicated a significant difference (p < 0.05), and the R² value of 0.62 demonstrated that the lecture method contributed 62% to the improvement of moral value implementation. The lecture method was proven to function not merely as a means of delivering learning material but also as a medium for internalizing moral values based on religious teachings.